Clinical Characteristics, In Silico Analysis, and Intervention of Neonatal-Onset Inflammatory Bowel Disease With Combined Immunodeficiency Caused by Novel TTC7A Variants - Chen, Yun-e; Chen, Jingfang; Guo, Wenxing; Zhang, Yanhong; Li, Jialing; Xie, Hui; Shen, Tong; Ge, Yunsheng; Huang, Yanru; Zheng, Wenying; Lu, Mei (Frontiers in Genetics, 2022)
We aimed to explore the genotypic and phenotypic characteristics of neonatal-onset inflammatory bowel disease (IBD) with combined immunodeficiency due to TTC7A mutation. We examined the clinical manifestations, imaging results, endoscopic and histological findings, interventions, and prognosis of a proband with neonatal-onset IBD and performed biochemical analyses, whole-exome sequencing (WES), and in silico analysis. Our proband developed severe early-onset diarrhea, malnutrition, electrolyte imbalance, dehydration, and recurrent infections after birth. Radiographic and ultrasonic images showed no specific manifestations. Endoscopic and histological examination revealed chronic inflammation. Immune function examination indicated immunodeficiency. WES identified compound heterozygous TTC7A mutations (c.2355+4A>G, c.643G>T) in the proband. In the expression analysis, no abnormal splicing in the TTC7A sequence was observed due to the c.2355+4A>G mutation; however, the mRNA expression was reduced. The proband’s condition did not improve after treatment with methylprednisolone or leflunomide. The proband died when treatment was stopped at the age of 5 months and 19 days. Compound heterozygous mutations (c.2355+4A>G, c.643G>T) in the TTC7A gene are described and verified for the first time. Our report expands the phenotypic spectrum of TTC7A mutations and the genotypic spectrum of very early-onset IBD with combined immunodeficiency.